Particle Oxidation Time for the Manufacture of Binderless Particleboard - Suhasman Suhasman; Muh. Yusram Massijaya; Yusuf Sudo Hadi; Adi Santoso (Wood Research Journal, 2011)
The oxidation treatment using hydrogen peroxide and ferrous sulphate of wood particles can form free radicals of the wood chemical components essentially required in manufacturing binderless particleboard. The oxidation process is expected to have a certain optimal time. Therefore, the purpose of this study was to analyze relationship between the oxidation time and the characteristic of produced binderless particleboard. Three wood species from community forest, namely, sengon (Paraserianthes falcataria), gmelina (Gmelina arborea), and mindi (Melia azedarach) were used for treatment. The air-dried wood particles of 10~20 mesh in size were oxidized using 20% hydrogen peroxide based on particle dry-weight and 5% ferrous sulphate based on hydrogen peroxide weight. The oxidized particles were conditioned in room at different periods of time (15, 30, 45, 60, 75, and 90 min) prior to the board production. The oxidized and conditioned particles were then hot-pressed at 180°C for 15 min with a specific pressure of 25 kgf cm-2.Results showed that oxidation treatment for 15 min was sufficient to produce a binderless particleboard with good physical and mechanical properties. The characteristics of the particleboard, such as dimensional stability, modulus of rupture, modulus of elasticity, and internal bond were equivalent to that of particleboard made of particles with a longer oxidation time. The particle board made of sengon showed excellent thickness swelling (only 5.04%) and modulus of elasticity (37.184 kgf cm-2). This research result indicated that sengon was the most suitable raw material for binderless particleboard production compared to other observed wood species.